The Evolution of Consumer Behavior in the Digital Age: A Review Perspective - Paryani Sunit N (AG Volumes, 2025)
Along with technological, sociological, and cultural developments, consumer behavior patterns in the digital era exhibit substantial transformations. Customers are calling for more individualized experiences that align with their beliefs, from experiential consumption to a preference for sustainable goods. The evolution of consumer behavior in the digital era, the effects of digital transformation on consumer behavior, and the variables influencing consumer behavior in the digital age were all covered in this article. This article concluded that consumer behavior in the digital age has shifted dramatically due to technology, e-commerce, and rising expectations for convenience and personalization. Consumers increasingly rely on digital platforms, social media, and mobile commerce to make informed decisions. Gender differences, trust, security, and online reviews influence purchases. Businesses must adopt data-driven, omnichannel, and customer-centric strategies to stay competitive in this evolving landscape